PENGARUH EMPLOYEE ENGAGEMENT DAN WORK-LIFE BALANCE TERHADAP KINERJA KARYAWAN MELALUI KEPUASAN KERJA PADA PTPN IV KEBUN PABATU KEC. DOLOK MERAWAN, KAB. SERDANG BEDAGAI - Putri, Urchillah; Anggraini; Rika Surianto Zalukhu; Limega Candrasa (JURNAL ILMIAH EDUNOMIKA, 2025)
This study aims to analyze the effect of Employee Engagement and Work Life Balance on employee performance through job satisfaction. The variables studied include Employee Engagement and Work Life Balance as independent variables, Employee performance as dependent variables, and job satisfaction as intervening variables. The study was conducted on employees of PTPN VI Kebun Pabatu, Dolok Merawan District, Serdang Bedagai Regency. The number of research samples was 51 people, determined using the Taro Yamane formula. This study uses primary data obtained by using questionnaires distributed to employees. The data analyzed using the path analysis method. The results of the study showed that Employee Engagement did not have a significant effect on Job Satisfaction, while Work-Life Balance had a significant effect on Job Satisfaction. Furthermore, Employee Engagement was proven to have a significant effect on Employee Performance, while Work-Life Balance did not have a significant effect on Employee Performance. This study also found that Job Satisfaction had a significant effect on Employee Performance. In addition, Job Satisfaction was able to mediate the effect of Employee Engagement on Performance, but was unable to mediate the effect of Work-Life Balance on Performance.